Dissection of flagellar pocket function in Trypanosoma brucei - Whipple, Sarah (2018)
To survive in the host bloodstream, the extracellular protozoan parasite Trypanosoma brucei must perform the critical cellular processes of nutrient uptake and secretion, whilst evading the host immune system. Central to this is the compartmentalisation of the parasite surface membrane into biochemically and functionally distinct domains. One of these domains, the flagellar pocket (FP), is the only region of the parasite surface competent for endo- and exocytosis and, as such, forms the primary site of exchange and communication between the parasite and its host. The overall importance of the FP for parasite virulence, and the essentiality of the few FP receptors characterised to date, make proteins that reside at this interface potentially attractive therapeutic targets. The identification of novel FP proteins, as part of a recent surface proteomics study, has provided a large set of putative receptors and transporters to explore and, as part of this thesis, I present work towards their functional characterisation. To this end, I carried out individual knockdown of 13 FP components by RNA interference. This revealed that ablation of these proteins was not detrimental to parasite survival in vitro, implying they could instead have critical functions in host-parasite interactions in vivo. Potential determinants of protein sorting to the FP were also investigated. FP localisation was seemingly independent of protein topology, or identifiable amino acid sequence motifs. Thus I examined the potential role of N-glycosylation in this process. Enzymatic treatment revealed that most FP proteins studied here were glycosylated, yet the type of N-glycan modification alone could not be used to predict surface domain localisation. On the other hand, knockdown of a key component of the flagellar pocket collar, which forms a putative barrier between the FP and cell body membranes, caused the mis-localisation of some resident FP proteins. This suggests a role for the collar in FP protein retention. Furthermore, movement of macromolecules in and out of the protected environment of the FP has been suggested to require motor proteins. In agreement with this, I hereby show that overexpression of a non-functional variant of Kinesin-17, which localises to the FP region, is detrimental to parasite survival. Overall the work presented in this thesis provides new insights into the mechanisms of FP membrane specialisation in T.brucei, highlights potential protein redundancy at this region, and begins to characterise the function of a novel FP-localised kinesin.